Extreme Spectral Richness in the Eye of the Common Bluebottle Butterfly, Graphium sarpedon - Chen, Pei-Ju; Awata, Hiroko; Matsushita, Atsuko; Yang, En-Cheng; Arikawa, Kentaro (Frontiers in Ecology and Evolution, 2016)
Butterfly eyes are furnished with a variety of photoreceptors of different spectral sensitivities often in species-specific manner. We have conducted an extensive comparative study to address the question of how their spectrally complex retinas evolved. Here we investigated the structure and function of the eye of the common bluebottle butterfly (Graphium sarpedon), using electrophysiological, anatomical and molecular approaches. Intracellular electrophysiology revealed that the eye contains photoreceptors of fifteen distinct spectral sensitivities. These can be divided into six spectral receptor classes: ultraviolet- (UV), violet- (V), blue- (B), blue-green- (BG), green- (G), and red- (R) sensitive. The B, G and R classes respectively contain three, four and five subclasses. Fifteen is the record number of spectral receptors so far reported in a single insect eye. We localized these receptors by injecting dye into individual photoreceptors after recording their spectral sensitivities. We thus found that four of them are confined to the dorsal region, eight to the ventral, and three exist throughout the eye; the ventral eye region is spectrally richer than the dorsal region. We also identified mRNAs encoding visual pigment opsins of one ultraviolet, one blue and three long wavelength-absorbing types. Localization of these mRNAs by in situ hybridization revealed that the dorsal photoreceptors each express a single opsin mRNA, but more than half of the ventral photoreceptors coexpress two or three L opsin mRNAs. This expression pattern well explains the spectral organization of the Graphium compound eye.